2022
DOI: 10.1186/s43045-022-00256-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on children

Abstract: Background The COVID-19 global pandemic has spread throughout the world, posing an extremely dangerous health risk for almost everyone. While dealing with such a large-scale viral disease, the healthcare infrastructure is under strain. Young adults who were thought to have been clinically affected fared better than their older counterparts. This pandemic has affected millions of children, especially those from low-economic backgrounds, who are otherwise highly susceptible and underprivileged. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Some strong risk factors were found like intergenerational chain of child abuse and low socioeconomic status, but practical intervention is not possible. The negative impacts of COVID-19 have been widely studied, and this result might be one of the risks for increased stress, especially toward their families in particular situations ( Amin & Parveen, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some strong risk factors were found like intergenerational chain of child abuse and low socioeconomic status, but practical intervention is not possible. The negative impacts of COVID-19 have been widely studied, and this result might be one of the risks for increased stress, especially toward their families in particular situations ( Amin & Parveen, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The negative impacts of child abuse are maintained throughout the victims’ lifespan, and result in various mood disorders, anxiety disorders, suicidal behavior, and the intergenerational cycle of child abuse ( Chapman et al, 2004 ; Fujiwara & Kawakami, 2011 ; Stickley et al, 2020 ; Horikawa et al, 2016 ; Berlin, Appleyard & Dodge, 2011 ). Many studies have concluded that more attention to child abuse is necessary during the COVID-19 pandemic because some risk factors such as mental stress, economic stress, social isolation, and a decrease in the chances of detecting child abuse must be reinforced by the pandemic ( Romanou & Belton, 2020 ; Pereda & Díaz-Faes, 2020 ; Brown et al, 2020 ; Amin & Parveen, 2022 ).…”
Section: Introductionmentioning
confidence: 99%